How women rise: break the 12 habits holding you back - Helgesen Sally; Goldsmith, Marshall (United Kingdom: Penguin Random House, 2019)
"How Women Rise" by Sally Helgesen and Marshall Goldsmith identifies 12 common habits that can hinder women's career advancement. The book provides real-life stories and research-based insights to help women overcome these barriers and reach their full potential. It emphasizes the importance of changing ingrained behaviors, claiming achievements, embracing assertiveness, and letting go of perfectionism to advance in their chosen fields.
Includes index
nmn, 10/06/2025
Loans
Keywords: Women Psychology; Career development; Self-actualization (Psychology); Sex role in the workplace; Motivation for women; Success in business